Online Mathematics Education during the COVID-19 Pandemic: Didactic Strategies, Educational Resources, and Educational Contexts - Ronnie Videla; Sebastián Rossel; Coralina Muñoz; Claudio Aguayo (MDPI AG, 2022)
One of the impacts of the COVID-19 pandemic has been restrictions on mobility and thus the closure of schools. This has had consequences on the teaching strategies of primary mathematics educators who were not familiar with online education. Most schools in Chile have adopted virtual and hybrid classes to continue educational processes. From a quantitative approach with a sample of n = 105 primary school educators and through an online survey, we analyzed how educators implemented the mathematics curriculum during the pandemic using various didactic strategies and educational resources, as well as their respective contexts. The results show that there is a relationship between the level of technical knowledge of teachers, the years of experience, and the types of teaching strategies they use. Likewise, differences were found between educators in rural and urban sectors according to the use of teaching strategies and the types of educational resources used. Regarding the didactic strategies, it is shown that the emerging strategies most used are metaphorical and analogical, whereas in traditional strategies the automation of procedures is imposed. The implications for practice include suggestions and guidelines for improving the training and professional development of mathematics teachers including increasing and strengthening the number and quality of teachers' didactic strategies and online pedagogical management skills and promoting metacognition through virtual forums. Finally, we discuss the context of the use of didactic strategies in mathematics during the pandemic, analyzing its challenges and opportunities.